2017
DOI: 10.12973/ejmste/80945
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and its Potential Impacts on Multicultural Education in Turkey

Abstract: The purpose of this study is to learn the perceptions of social media users regarding multicultural education in Turkey. With this goal in mind, a short film was created that summarized the issue of multicultural education, which was shared via social media. After viewing the film, the views of the participants who had expressed comments concerning multicultural education were taken for evaluation, and 95.65% of participants harbored positive perceptions about multicultural education. Furthermore, the collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Personal traits such as a high internal locus of control, goaldirectedness, and altruism developed a resourcefulness to convert life experiences into useful skills transferrable in the school setting. Previous studies suggest that these protective factors decreased negative effects brought about by risk factors (Carlson et al, 2012;Damgaci & Aydin, 2018;Perkins & Jones, 2004). The personal protective factors encouraging academic success among this study's student participants resembled those found in Benard's (1991) research on resilient children, including: high internal locus of control, personal competence, religiosity and spirituality, and caring relationships with family and others.…”
Section: Discussionsupporting
confidence: 73%
“…Personal traits such as a high internal locus of control, goaldirectedness, and altruism developed a resourcefulness to convert life experiences into useful skills transferrable in the school setting. Previous studies suggest that these protective factors decreased negative effects brought about by risk factors (Carlson et al, 2012;Damgaci & Aydin, 2018;Perkins & Jones, 2004). The personal protective factors encouraging academic success among this study's student participants resembled those found in Benard's (1991) research on resilient children, including: high internal locus of control, personal competence, religiosity and spirituality, and caring relationships with family and others.…”
Section: Discussionsupporting
confidence: 73%
“…They were comfortable with teaching about the environment and other cultures and concentrated on the self-esteem building, interpersonal and cooperative element of the world studies approach that would promote good citizenship to teaching global citizenship components (Davies et al, 1999). Given, as students highlighted, that most descriptions of education for global citizenship stress the importance of democracy and human rights (Damgaci & Aydin, 2018;Davies, 2004;Ibrahim, 2005;Lafer & Aydin, 2012), if students are to be educated in and for global citizenship, e.g., will be aware universal values, have a positive view of diversity, will avoid racism, stereotypes, and will be open-minded and appreciate one another, these principles suggest that students should experience democracy, social justice, and human rights in their daily lives at school -and not just be told about it. Almost all students believe that it is important to learn about global issues at school and that young people need to understand global matters in order to make choices about how they want to lead their lives in the future.…”
Section: Results Of Qualitative Data Analysismentioning
confidence: 99%
“…The participants’ outlook toward multicultural education changed within the levels of awareness, the acknowledgment of gaps in personal knowledge, and the opportunities for future learning and dispelling the previous mindset. This change in outlook is important because the recent growth of ethnic groups has created the need for increased awareness in diverse classroom settings and highlighted the importance of teaching multiculturalism (Damgaci & Aydin, 2018; Erbas, 2019). It was expressed that the outlook of a doctoral student was only impacted after taking these courses; however, if they were offered earlier, students could pursue more diversity and multicultural education-based classes as electives.…”
Section: Discussionmentioning
confidence: 99%